Wither nepad African and nepad Nigeria? A preliminary study of similarities and differences. - Mamman Saba, Abdulkadir; Jawan, Jayum; Ahmad, Zaid; Abu Samah, Asnarulkhadi (The Journal of International Social Research, 2011)

(untitled)
The New Partnership for Africa's Development (NEPAD), is the latest in a long line of policy frameworks intended to place Africa on a path of sustainable growth and development. The picture of Africa in the 21st century has been characterized by daunting challenges of economic underdevelopment, poverty, political instability, civil wars, and diseases. The idea of introducing an Indigenous African Approach, (IAA), to problems peculiar to Africa came after the social-political and economic realities of the continent had defied several developmental plans, which were said to be alien to Africa or drafted by expert and institutions that fail to appreciate the peculiarities of the continent. Thus, it is imperative to understand what NEPAD stands for in Africa and see how NEPAD operates in Nigeria. This preliminary study established a clear distinction and inconsistency between NEPAD Africa and NEPAD Nigeria. Furthermore, the study determined the level of inconsistency and lack of political will of African leaders in implementing NEPAD objectives. The findings of the study also revealed that there is lack of awareness and sound knowledge about NEPAD programme in Africa in general and in Nigeria in particular. Correlational analyses found that ignorance, lack of commitments, fund and corruption were associated with all facets of NEPAD activities in Nigeria. The results provide evidence that the greatest challenge of NEPAD Nigeria is leadership problem. It must be noted that findings of this preliminary study were based on data collected through observation, in-depth interviewing, Focus Group Discussion (FGD) and nominal interviewing. All of these were possible using Qualitative approach and exploratory design technique. A sample size of the respondents (n= 60) were small however, a bigger sample size would be required to represent larger population in future studies.